A homozygous protein-truncating mutation in ACTL7A causes male infertility characterized by fertilization failure. Issue 3 (30th September 2022) - Chen, Yao; Chen, Biao-Bang; Sang, Qing; Wang, Lei; Zhao, Jun-Li; Sun, Xiao-Xi
Abstract : Objective: This study aimed to screen for novel mutations in ACTL7A and expand the spectrum of known mutations responsible for recurrent fertilization failure. Methods: Whole-exome sequencing was performed on samples from couples who experienced recurrent assisted reproductive technology failure and visited the General Hospital of Ningxia Medical University. Western blotting and quantitative Real-time PCR were used to investigate the effects of the mutation on HEK293T cells. Results: Samples from 12 couples with total fertilization failure or poor fertilization (fertilization rate <20%) were subjected to whole-exome sequencing, and a novel homozygous protein-truncating mutation (c. 1101dupC, p. S368Qfs*5) in ACTL7A was identified in a patient with recurrent poor fertilization. The mutant resulted in a truncated protein as well as decreased protein expression level in HEK293T cells. Conclusions: Our findings expand the mutational and phenotypic spectrum of ACTL7A, thus providing a potential diagnostic marker for fertilization failure due to male factors.